2016
DOI: 10.1016/j.gloplacha.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationarity in the occurrence rate of floods in the Tarim River basin, China, and related impacts of climate indices

Abstract: Amplification of floods in the Xinjiang, China, has been observed, but reports on their changing properties and underlying mechanisms are not available. In this study, occurrence rates of floods in the Tarim River basin, the largest inland arid river basin in China, were analyzed using the Kernel density estimation technique and bootstrap resampling method. Also analyzed were the occurrence rates of precipitation extremes using the POT (Peak over Threshold)-based sampling method. Both stationary and non-statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…Thus the nonstationarities in the occurrence of extreme events such as floods, heavy precipitation events and tropical storms have received more attention, because estimations of these extreme event occurrence rates are related to model the dynamics of many ecological, social and economic processes (Villarini et al ., , ; Silva et al ., ; Gu et al ., , ; Mumby et al ., ). The major aims of the present study are to carry out an exploratory analysis on the variability of frequency of heavy precipitation across China by concerning the occurrence rates of heavy precipitation events (HPOR), and ascertain if the variability obeys the assumption of nonstationarity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the nonstationarities in the occurrence of extreme events such as floods, heavy precipitation events and tropical storms have received more attention, because estimations of these extreme event occurrence rates are related to model the dynamics of many ecological, social and economic processes (Villarini et al ., , ; Silva et al ., ; Gu et al ., , ; Mumby et al ., ). The major aims of the present study are to carry out an exploratory analysis on the variability of frequency of heavy precipitation across China by concerning the occurrence rates of heavy precipitation events (HPOR), and ascertain if the variability obeys the assumption of nonstationarity.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that variation of flood across Australia is closely connected to the climate system and the climate indices have a remarkable impact on the variation FMF through their effects on atmospheric circulation. The change of SST has played a key role to the variation of extreme precipitation and floods events (Gu et al, ; Liu et al, ; Meredith et al, ; Zhang et al, ). However, generating floods are determined by multiple factors such as rainfall intensity, antecedent soil moisture, catchment area, catchment soil properties, and catchment slope.…”
Section: Resultsmentioning
confidence: 99%
“…The reliability of flood predictions is mainly dependent on the selected climate indices (Mallakpour & Villarini, 2016). It is challenging to choose the dominant climate index for predicting flooding (Gu et al, 2016;Risko & Martinez, 2014). However, identifying the dominant climate index is important for investigating the physical causalities behind the observed relationships (Gu et al, 2016;Mallakpour & Villarini, 2016;Xiao et al, 2015;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on daily precipitation and temperature dataset of 23 gauging stations and annual streamflow data of five hydrological stations covering 1960-2005, Zhang et al (2010) analyzed spatio-temporal variations of climatic change and associated impacts on water resource and found that annual streamflows of headstream rivers, except Aksu River, did not exhibit significant trends [17,18]. analyzed the intra-annual, seasonal and inter-seasonal clustering of floods and investigated possible impacts of climate indices on the occurrence rates of floods [19,20]. Li et al (2016) developed a new agricultural drought index, which is based on the Variable Infiltration Capacity (VIC) model coupled with an irrigation scheme and a reservoir module.…”
Section: Introductionmentioning
confidence: 99%